Assessing the re-use potential of research data in empirical educational research - Claudia Neuendorf; Malte Jansen; Lisa Pegelow (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2020)
In the last decade, the call for sharing research data has intensified within the educational research community in Germany. This development has taken place within the professional communities and it has been spurred by research funding organizations mandating researchers to share their research data. However, researchers and data centers alike are aware that not all data might be fit for re-use. Therefore, research data should be evaluated with respect to their analytical potential for re-use. Yet, criteria and processes for identifying data with high re-use potential are lacking. Thus, a workshop on the topic "Re-use potential of research data" was held on June 19th, 2018, at the Institute for Educational Quality Improvement, which was organized within the German Network for Educational Research Data (Verbund Forschungsdaten Bildung, VerbundFDB). Participants were ten researchers from different disciplines of empirical educational research in Germany. Representatives from the educational sciences, psychology, economics and sociology were present. The aim of the workshop was to develop and discuss quality criteria for research data from the perspective of secondary users of research data.
Keywords: 330; Forschungsdaten; Bildungsforschung